2005
DOI: 10.1038/sj.onc.1209143
|View full text |Cite
|
Sign up to set email alerts
|

IGF2 is critical for tumorigenesis by synovial sarcoma oncoprotein SYT-SSX1

Abstract: Synovial sarcoma is an aggressive soft tissue tumor characterized by a specific chromosomal translocation between chromosome 18 and X. This translocation can generate a fusion transcript encoding SYT-SSX1, a transforming oncoprotein. We present evidence that SYT-SSX1 induces insulin-like growth factor II expression in fibroblast cells. SYT-SSX2, a fusion also frequently found in synovial sarcoma, is necessary for maintaining Igf2 expression in the synovial sarcoma cell line, and the increased IGF2 synthesis pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
60
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 49 publications
1
60
0
Order By: Relevance
“…Due to the heterogeneity of sarcoma, >100 distinct subtypes have been described to date, with new subtypes frequently reported (4). Synovial sarcoma, a soft-tissue tumor, is characterized by a reciprocal t(X;18) translocation, in which the SS18 gene on chromosome 18 fuses with the SSX1, SSX2 or, less commonly, SSX4 gene on the X chromosome (5,6). Ewing's sarcoma has a relatively simple genetic signature, consisting of a t(11;22) translocation (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the heterogeneity of sarcoma, >100 distinct subtypes have been described to date, with new subtypes frequently reported (4). Synovial sarcoma, a soft-tissue tumor, is characterized by a reciprocal t(X;18) translocation, in which the SS18 gene on chromosome 18 fuses with the SSX1, SSX2 or, less commonly, SSX4 gene on the X chromosome (5,6). Ewing's sarcoma has a relatively simple genetic signature, consisting of a t(11;22) translocation (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…TUNEL and in Vivo Tumor Formation Assay-TUNEL assay on cells grown in methylcellulose was performed as described (23). Tumor formation assay in immunocompromised mice was done also as described (23) with the measurement of tumor volume as the (1/2)L1(L2) 2 where L1 is the long axis and L2 is the short axis of the tumor mass measured with a caliper in millimeter.…”
mentioning
confidence: 99%
“…Tumor formation assay in immunocompromised mice was done also as described (23) with the measurement of tumor volume as the (1/2)L1(L2) 2 where L1 is the long axis and L2 is the short axis of the tumor mass measured with a caliper in millimeter.…”
mentioning
confidence: 99%
“…This could In synovial sarcoma, in vitro studies have found that the SS18-SSX oncogene induces IGF2 expression which seems critical to convey tumorigenic properties. [48][49][50] IGF2 expression was associated with both the ÀSSX1 and ÀSSX2 translocation subtypes. 48 In this study, we present evidence that in primary synovial sarcoma tumor specimens, IGF2 is highly expressed at the protein level, supporting translational relevance to patients of these experimental findings, and attempts to target this pathway in patients using IGF signaling inhibitors.…”
Section: Discussionmentioning
confidence: 97%